2015
DOI: 10.1212/wnl.0000000000001502
|View full text |Cite
|
Sign up to set email alerts
|

Acute infarcts cause focal thinning in remote cortex via degeneration of connecting fiber tracts

Abstract: Objective: To study remote effects distant from acute ischemic infarcts by measuring longitudinal changes of cortical thickness in connected brain regions as well as changes in microstructural integrity in connecting fiber tracts.Methods: Thirty-two patients (mean age 71 years) underwent a standardized protocol including multimodal MRI and clinical assessment both at stroke onset and 6 months after the event. Cortex connected to acute infarcts was identified by probabilistic diffusion tensor tractography start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
128
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(165 citation statements)
references
References 40 publications
17
128
1
3
Order By: Relevance
“…First, in the present study, we found that CC A is independently associated with the volume of lacunes, suggesting that reduction of CC A might be secondary to degeneration of long-range fibers passing through the altered parenchyma, in line with the description of remote cortex atrophy after subcortical infarcts. 19 Note that we observed, in 10 of 26 patients, imaging aspects compatible with such secondary changes after the occurrence of lacunes in the corpus callosum fibers (Fig 3). Also, in additional analyses, we compared 28 other patients with CADASIL without lacunes from our national cohort study who were age-and sex-matched to the control group of the present study.…”
Section: Discussionsupporting
confidence: 51%
“…First, in the present study, we found that CC A is independently associated with the volume of lacunes, suggesting that reduction of CC A might be secondary to degeneration of long-range fibers passing through the altered parenchyma, in line with the description of remote cortex atrophy after subcortical infarcts. 19 Note that we observed, in 10 of 26 patients, imaging aspects compatible with such secondary changes after the occurrence of lacunes in the corpus callosum fibers (Fig 3). Also, in additional analyses, we compared 28 other patients with CADASIL without lacunes from our national cohort study who were age-and sex-matched to the control group of the present study.…”
Section: Discussionsupporting
confidence: 51%
“…Also, using quantitative measures for hippocampal [45], gray matter, and white matter atrophy (instead of using a single quantitative measure for global atrophy as was done in the current study) might help to further increase the explained variance in cognitive functioning. Assessing regional gray matter atrophy might be particularly interesting in relation to the DTI-based assessment of strategic white matter tracts, since subcortical vascular lesions are known to cause focal cortical thinning via secondary degeneration [46]. An effort to acquire and integrate all these data into a large cohort in order to push the explained variance in cognitive functioning to a maximum would be interesting, but also very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…A delayed apoptotic cell death occurs in the thalamus in experimental stroke models after cortical stroke that is distant to the thalamus [87], and similarly in the substantia nigra after striatal stroke that is distant from the substantia nigra [81]. After white matter stroke, connected cortical areas suffer a delayed damage that is seen as cortical thinning in magnetic resonance imaging [88], and as an overall brain atrophy [89]. In the aged brain with white matter stroke there is increased microglial activation and inflammatory cytokine release in connected cortical areas, compared with the young adult [90].…”
Section: Relayed Stroke: Effects Of Ischemia On Distant Connected Bramentioning
confidence: 99%